Managing expectations for the Rotary Club of Antipolo East using a communication management toolkit and seminar - Sasuman, Angelika Bulaong (Animo Repository, 2023)
The Rotary Club of Antipolo East (RCAE) is an organization that focuses on providing humanitarian aid to the community of Antipolo East, specifically Barangay San Jose and San Luis. RCAE also aligns their organization and service projects to their motto, “Service Above Self,” contributing to their goal of being perceived as equal, diverse, and inclusive towards their stakeholders and members. However, according to the communication audit results, RCAE’s current online communication practices on Facebook only focus on their expectations, resulting in the organization being unaware of their stakeholders’ expectations. As a result, the public perceives the organization as an exclusive club with golf members as RCAE’s online communication contains posts filled with happy birthday messages, club meetings or activities, and insufficient information on service projects. To address the organizational communication problem of RCAE, the thesis group proposed a communication management toolkit guided by Olkkonen and Luoma-aho’s (2015) expectation management theory. The toolkit includes publication materials, caption templates, Facebook mini-series videos, and a feedback form. The group also conducted a one-day seminar with RCAE to discuss the communication management toolkit and the importance of expectation management in their online communication. To analyze the toolkit’s results, the group presented Facebook mock-ups and organizational videos to the stakeholders and analyzed their responses from the feedback form. The results revealed that RCAE’s online communication practices improved because the stakeholders perceived them as an accommodating and inclusive organization which means that the toolkit met the publics’ expectations.